1976
DOI: 10.1116/1.568967
|View full text |Cite
|
Sign up to set email alerts
|

Angular-dependent Ne+-ion scattering from a solid Au target

Abstract: Ion-scattering spectroscopy (ISS) is a technique used for composition analysis of solid surfaces. The angular dependence of low-energy ion scattering has been investigated in order to assess the possibility of using large scattering angles in ISS. The equipment used for these experiments is described. It allows for measurements of the angular dependence of the scattering process between 0° and 150°. A detailed discussion of the special ion optical design of the primary beam train and the analyzing system for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1977
1977
1981
1981

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In general it is not possible to separate these contributions except by a process of fitting experimental results to theoretical equations. For example, Brongersma et al (1976) suggested the neutralization factor could be written Verheij et al (1976) have analysed a similar situation in considerably more detail. An overall variation of ion yield with a parameter such as energy, angle of incidence or angle of exit is then fitted by an equation similar to or more complex than equation (lO).…”
Section: Neutralizationmentioning
confidence: 99%
“…In general it is not possible to separate these contributions except by a process of fitting experimental results to theoretical equations. For example, Brongersma et al (1976) suggested the neutralization factor could be written Verheij et al (1976) have analysed a similar situation in considerably more detail. An overall variation of ion yield with a parameter such as energy, angle of incidence or angle of exit is then fitted by an equation similar to or more complex than equation (lO).…”
Section: Neutralizationmentioning
confidence: 99%